Evaluating GCS and FOUR score in predicting mortality of Traumatic Brain Injury Patients (TBI): A prospective study in a tertiary hospital of South Malabar - K V Anand; P T Shahid; K K Shameel (Wolters Kluwer Medknow Publications, 2024)
Objective: This study evaluated the full outline of Unresponsiveness (FOUR) score and Glasgow Coma Scale (GCS) to predict traumatic brain injury (TBI) outcomes. Methods: Among 107 patients, FOUR and GCS grading systems analyzed emergency department patients within 24 hours. FOUR and GCS were assessed simultaneously. Patients were followed for 15 days/discharge/death to evaluate the results. Modified Rankin scores measured in-hospital mortality, morbidity, and stay. Results: 65.42% of patients were 25-65. 10% were under 25, and 25% were over 65. Patients were 81% male. Road traffic accidents (RTAs) (90%), falls (7.48%), and assaults (1.47%) caused TBI. 19.62% died. 85.7% of 21 non-survivors had GCS <5 and FOUR <4. GCS mortality sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 85.71%, 93.02%, 75, and 96.4 (P < 0.0001). FOUR score mortality sensitivity, specificity, PPV, and NPV were 85.71%, 96.51%, 85.7, and 96.5 (P < 0.0001). GCS and FOUR AUCs matched (P = 0.52). The unadjusted model reduced in-hospital mortality by 14% for every one point increase in GCS. Every 1-point FOUR score increase reduced in-hospital mortality by 40% in the unadjusted model. GCS and FOUR scored 0.9 Spearman. Conclusion: The FOUR score was comparable in the prediction of mortality in these patients.